Chemical compensation to mechanical loss in cell mechanosensation - Qin Ni; Zhuoxu Ge; Anindya Sen; Yufei Wu; Jinyu Fu; Alice Amitrano; Nitish Srivastava; Konstantinos Konstantopoulos; Sean X. Sun (Proceedings of the National Academy of Sciences, 2025)
Mammalian cells sense and respond to environmental changes using a complex and intelligent system that integrates chemical and mechanical signals. The transduction of mechanical cues into chemical changes modulates cell physiology, allowing a cell to adapt to its microenvironment. Understanding how the chemical and mechanical regulatory modules interact is crucial for elucidating mechanisms of mechanosensation and cellular homeostasis. In this study, we find that cells exhibit nonmonotonic changes in cell volume and intracellular pH when subjected to physical stimuli and varying degrees of actomyosin cytoskeleton disruption. We find that these nonmonotonic responses are mediated by a chemical compensation mechanism, where the attenuation of actomyosin activity stimulates the activity of PI3K/Akt pathway. This, in turn, activates sodium-hydrogen exchanger 1 (NHE1), resulting in elevated intracellular pH and increased cell volume. Furthermore, we identify a competitive interaction between the PI3K/Akt and MAPK/ERK pathways—two major regulators of cell proliferation and motility. This competition modulates the chemical compensation based on the relative activities of these pathways. Our mathematical modeling reveals the network structure that is essential for establishing the nonmonotonic response. Interestingly, this regulatory system is altered in HT1080 fibrosarcoma, highlighting a potential mechanistic divergence in cancer cells in contrast to their normal-like counterpart, such as NIH 3T3 and HFF-1 fibroblasts. Overall, our work reveals a compensatory mechanism between chemical and mechanical signals, providing an infrastructure to elucidate the integrated mechanochemical response to environmental stimuli.